On the Rational Approximation of Analytic Functions Having Generalized Types of Rate of Growth - Devendra Kumar (International Journal of Mathematics and Mathematical Sciences)
The present paper is concerned with the rational approximation of functions holomorphic on a domain G⊂C, having generalized types of rates of growth. Moreover, we obtain the characterization of the rate of decay of product of the best approximation errors for functions f having fast and slow rates of growth of the maximum modulus.